Analysis of microenterprise lending in Ecuador: a study of determinant factors - Montero Reyes, Yilena; Gallardo Solís, Joanna Maricela; Toalombo Capuz, María Magdalena; Moscoso Jurado, David Estuardo (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
This work of literature review and evaluative critical analysis is directed to the analysis of lending to microenterprises in Ecuador and the ability to reflect on strategies that may be established as tools that allow greater efficiency in the development of lending activities in different organizations such as banks, credit unions, and others that operate throughout the country. It is for this reason that will deepen theoretical and conceptual aspects related to the financial system and introduction to credit as a basis for further analysis of the loan portfolio. Constitute the premises for the analysis and evaluation of the 5 C credit lending process in microenterprise where findings and irregularities that are common and can affect this process are indicated. Similarly, strategies in the credit field for indicating micro policies, procedures and other conditions for a successful and efficient credit granting process are presented.